The Peculiarities of Memoirs Written in the Vortex of Tragic Events - Tūtlis, Vidmantas (Genocidas ir rezistencija, 1997)
This article uses memoirs and diaries of famous partisans to analyse the circumstances of their formation, peculiarities, similarities, differences, and how they reflect armed resistance and the mentality of partisans.
Keywords: memoirs; partisans; diaries; Ramanauskas; Dzūkas